2022
DOI: 10.3389/fchem.2022.825716
|View full text |Cite
|
Sign up to set email alerts
|

The Surprisingly Positive Effect of Zinc-Phthalocyanines With High Photodynamic Therapy Efficacy of Melanoma Cancer

Abstract: Phthalocyanine (Pc) dyes are photoactive molecules that can absorb and emit light in the visible spectrum, especially in the red region of the spectrum, with great potential for biological scopes. For this target, it is important to guarantee a high Pc solubility, and the use of suitable pyridinium units on their structure can be a good strategy to use effective photosensitizers (PSs) for photodynamic therapy (PDT) against cancer cells. Zn(II) phthalocyanines (ZnPcs) conjugated with thiopyridinium units (1–3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 55 publications
0
8
0
1
Order By: Relevance
“…The fluorescence lifetime was determined on a Fluorescence Correlation Spectroscopy/Fluorescence Lifetime Imaging coupled to a laser with 420 nm excitation wavelength. Direct measurement of singlet oxygen was performed by luminescence method from Equation (2), as described in the literature [ 60 ], using ZnPc as standard (λ exc = 660 nm, Φ Δ = 0.56 in DMF) [ 61 , 62 ]. Φ Δ = Φ st (I s /I st ) where Φ Δ is the singlet oxygen quantum yield of the sample; Φ st the singlet oxygen quantum yield of ZnPc ; I st is the phosphorescence intensity of 1 O 2 at 1270 nm for ZnPc ; and I s the phosphorescence intensity for the sample.…”
Section: Methodsmentioning
confidence: 99%
“…The fluorescence lifetime was determined on a Fluorescence Correlation Spectroscopy/Fluorescence Lifetime Imaging coupled to a laser with 420 nm excitation wavelength. Direct measurement of singlet oxygen was performed by luminescence method from Equation (2), as described in the literature [ 60 ], using ZnPc as standard (λ exc = 660 nm, Φ Δ = 0.56 in DMF) [ 61 , 62 ]. Φ Δ = Φ st (I s /I st ) where Φ Δ is the singlet oxygen quantum yield of the sample; Φ st the singlet oxygen quantum yield of ZnPc ; I st is the phosphorescence intensity of 1 O 2 at 1270 nm for ZnPc ; and I s the phosphorescence intensity for the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning the t -Bu-substituted ones, no substrate conversion was observed with NiPCy t Bu 4 or MgPCy t Bu 4 , while ZnPCy t Bu 4 provided slow conversion to reach only 19% in 90 min. This result was rather surprising as Zn-phthalocyanines are among the most widely used phthalocyanines for 1 O 2 generation. , In comparison, the metal-free H 2 PCy t Bu 4 gave a better conversion of 52% in a 90 min reaction time. We were delighted to find out that Si­(OH) 2 PCy t Bu 4 and Si­(Cl) 2 PCy t Bu 4 gave good conversions of 75 and 78%, respectively, and PtPCy t Bu 4 and PdPCy t Bu 4 were even more reactive with 88 and 100% conversions, respectively, within the same reaction time presumably as a result of a higher TOF in the latter cases due to heavy-atom enhanced singlet-to-triplet ISC.…”
Section: Resultsmentioning
confidence: 99%
“…The studied GaPc was evaluated with a high photodynamic activity as compared to similar phthalocyanine complexes studied on pigmented melanoma cells [ 27 , 28 , 29 ]. A high photo-safety (low cytotoxicity) was determined for GaPc and for its conjugate on the tested model embryonal cell line BALB 3T3 for the concentrations which related to PDT usage ( Figure 3 a).…”
Section: Resultsmentioning
confidence: 99%
“…Other parameters calculated based on the photo- and dark cytotoxicity studies are following the Equations reported before [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Briefly, these are the phototherapeutic index (PI), cytotoxicity (CC50), photodynamic activity (PDA50), selectivity index (SI), and photo-irritation factor (PIF) calculated using the Formula (2): PIF = CC50 (−Irr)/CC50 (+Irr) where −Irr is the absence of light and +Irr is the presence of light.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation